2012
DOI: 10.1007/s00167-012-1911-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional knee brace use effect on peak vertical ground reaction forces during drop jump landing

Abstract: Prospective study, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…At increasing vertical height, the authors found a positive correlation with peak posterior GRF. At increasing horizontal height, the authors found a Table 1 Summary of biomechanical and neuromuscular evidence potentially related to aberrant knee mechanics in male athletes Sport Findings Joint kinetics Soccer Cutting maneuvers higher varus-valgus and internal-external knee moments than running (no differences in flexion-extension knee moments) [13] Side-step cutting elicited knee flexion, valgus, and IR loads, and crossover cutting elicits knee flexion, varus, and ER loads [13] Cutting maneuvers elicited higher foot loading in the medial aspect, and sprinting higher loading in the first and second ray [34] Basketball During side-step cutting, higher peak stance knee valgus moment was associated with higher initial contact hip flexion and IR, and knee valgus position [66] Soccer and basketball No longitudinal changes in peak knee abduction moments at landing in pubertal and post-pubertal athletes [40] Basketball and hockey Players wearing knee braces landed with lower peak vertical GRF compared with subjects without knee brace [80] American football Artificial turf higher peak pressures within central forefoot and lesser toes than natural grass, but the latter higher relative load within medial forefoot and lateral mid-foot [38] Australian football Ankle taping reduced knee IR and varus moments during running and side-step cutting in planned and unplanned situations [87] Combination Foot wide and torso towards the opposite direction of the side-step cut (technique modification) increased knee valgus and IR moment [27] Foot internally rotated during side-step cutting elicited lower flexion/extension moments compared with foot wide technique [27] Increased knee valgus at landing if the ball to catch is moving towards the preferred landing leg [25] Landing with foot and knee ER, hip abduction and IR, and lateral flexion of the trunk is associated with higher knee valgus and IR loads [25] Single-leg landing or increasing landing height produced higher peak GRF [5,105] Increasing landing height produced greater knee power and work [5] In single-leg landing, hip and ankle were the main energy dissipaters in sagittal plane, and knee the main energy dissipater in the frontal plane [106] In double-leg landing, hip and knee were the main energy dissipaters in sagittal plane, and hip the main energy dissipater in the frontal plane [106] In the frontal plane, single-leg landing had greater knee range of motion, moment, and energy dissipation compared with double-leg landing [106] Peak vertical and posterior GRF increased with greater vertical height at landing....…”
Section: Biomechanics: Sagittal Planementioning
confidence: 99%
See 1 more Smart Citation
“…At increasing vertical height, the authors found a positive correlation with peak posterior GRF. At increasing horizontal height, the authors found a Table 1 Summary of biomechanical and neuromuscular evidence potentially related to aberrant knee mechanics in male athletes Sport Findings Joint kinetics Soccer Cutting maneuvers higher varus-valgus and internal-external knee moments than running (no differences in flexion-extension knee moments) [13] Side-step cutting elicited knee flexion, valgus, and IR loads, and crossover cutting elicits knee flexion, varus, and ER loads [13] Cutting maneuvers elicited higher foot loading in the medial aspect, and sprinting higher loading in the first and second ray [34] Basketball During side-step cutting, higher peak stance knee valgus moment was associated with higher initial contact hip flexion and IR, and knee valgus position [66] Soccer and basketball No longitudinal changes in peak knee abduction moments at landing in pubertal and post-pubertal athletes [40] Basketball and hockey Players wearing knee braces landed with lower peak vertical GRF compared with subjects without knee brace [80] American football Artificial turf higher peak pressures within central forefoot and lesser toes than natural grass, but the latter higher relative load within medial forefoot and lateral mid-foot [38] Australian football Ankle taping reduced knee IR and varus moments during running and side-step cutting in planned and unplanned situations [87] Combination Foot wide and torso towards the opposite direction of the side-step cut (technique modification) increased knee valgus and IR moment [27] Foot internally rotated during side-step cutting elicited lower flexion/extension moments compared with foot wide technique [27] Increased knee valgus at landing if the ball to catch is moving towards the preferred landing leg [25] Landing with foot and knee ER, hip abduction and IR, and lateral flexion of the trunk is associated with higher knee valgus and IR loads [25] Single-leg landing or increasing landing height produced higher peak GRF [5,105] Increasing landing height produced greater knee power and work [5] In single-leg landing, hip and ankle were the main energy dissipaters in sagittal plane, and knee the main energy dissipater in the frontal plane [106] In double-leg landing, hip and knee were the main energy dissipaters in sagittal plane, and hip the main energy dissipater in the frontal plane [106] In the frontal plane, single-leg landing had greater knee range of motion, moment, and energy dissipation compared with double-leg landing [106] Peak vertical and posterior GRF increased with greater vertical height at landing....…”
Section: Biomechanics: Sagittal Planementioning
confidence: 99%
“…Rishiraj et al [80] evaluated the effects of a functional knee brace on peak GRF during drop-jump landing in male basketball and field hockey athletes. Players wearing prophylactic knee braces landed with significantly lower peak vertical GRF compared with players with no knee brace.…”
Section: Prophylactic Bracing/taping Evidencementioning
confidence: 99%
“… 10 , 26 , 27 As a result, ACL patients were more likely accommodated to the brace condition and responded differently than an individual wearing the brace for the first time. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Although bracing may have a beneficial impact performance initially, recent literature suggests that wearer accommodation to bracing is possible in terms of reaction, fatigue, and performance. 73,74 Though not studied, accommodation to bracing may apply to patients with ACL deficiency and those who have undergone ACL reconstruction.…”
Section: Clinical Efficacy Of Brace Use In Patients With Acl Deficienmentioning
confidence: 99%